Relaxing moral reasoning to win: How organizational identification relates to unethical pro-organizational behavior - Chen, Mo; Chen, Chao C; Sheldon, Oliver J (Journal of applied psychology, 2016)
Drawing on social identity theory and social-cognitive theory, we hypothesize that organizational identification predicts unethical pro-organizational behavior (UPB) through the mediation of moral disengagement. We further propose that competitive interorganizational relations enhance the hypothesized relationships. Three studies conducted in China and the United States using both survey and vignette methodologies provided convergent support for our model. Study 1 revealed that higher organizational identifiers engaged in more UPB, and that this effect was mediated by moral disengagement. Study 2 found that organizational identification once again predicted UPB through the mediation of moral disengagement, and that the mediation relationship was stronger when employees perceived a higher level of industry competition. Finally, Study 3 replicated the above findings using a vignette experiment to provide stronger evidence of causality. Theoretical and practical implications are discussed. (PsycINFO Database Record